2013
DOI: 10.1371/journal.ppat.1003243
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Mediates Immunopathology in the Absence of IL-10 Following Leishmania major Infection

Abstract: Leishmaniasis, resulting from infection with the protozoan parasite Leishmania, consists of a wide spectrum of clinical manifestations, from healing cutaneous lesions to fatal visceral infections. A particularly severe form of cutaneous leishmaniasis, termed mucosal leishmaniasis, exhibits decreased IL-10 levels and an exaggerated inflammatory response that perpetuates the disease. Using a mouse model of leishmaniasis, we investigated what cytokines contribute to increased pathology when IL-10-mediated regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
124
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 77 publications
13
124
1
2
Order By: Relevance
“…It is important also to note that the immune pathways associated with regulation of IL-17 are complex. For example, in support of our findings, opposing functions of IL-10 and various IL-17-producing cell types have been reported in other disease models, including infections (34,35) and, importantly, arthritis (36,37). However, cells which produce both cytokines exist (32,38), and IL-10-producing regulatory T (Treg) cells have also been shown to aid in the production of Th17 cells at certain periods of development (39).…”
Section: Discussionsupporting
confidence: 82%
“…It is important also to note that the immune pathways associated with regulation of IL-17 are complex. For example, in support of our findings, opposing functions of IL-10 and various IL-17-producing cell types have been reported in other disease models, including infections (34,35) and, importantly, arthritis (36,37). However, cells which produce both cytokines exist (32,38), and IL-10-producing regulatory T (Treg) cells have also been shown to aid in the production of Th17 cells at certain periods of development (39).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, it was reported that mice lacking the IL-17 receptor were defective in the long-term control of M. tuberculosis infection (156). On the other hand, M. tuberculosis and Salmonella infections are controlled normally in IL-23-deficient mice, in which Th17 generation does not occur (157,158), and neutralization of IL-17 had no effect on the control of L. major infection (159). Furthermore, people with mutations that affect the expression of IL-17 or IL-17 receptor are susceptible to Candida and Staphylococcus aureus skin infections (160) but do not appear to be susceptible to the phagosomal pathogens that afflict people lacking CD4 ϩ T cells or IL-12 receptor (27,28,161).…”
Section: Srivastava and Ernst Recently Shed Light On How The Interactmentioning
confidence: 99%
“…Support for a protective role for IL-17 comes from a study showing IL-17RA-deficient C57BL/6 mice infected with L. infantum harbored higher tissue parasite burdens than wild-type (WT) control mice (23). In contrast, IL-17 promoted the progression of cutaneous leishmaniasis in susceptible mice infected with L. major (24), whereas in IL-10-deficient mice infected with L. major, IL-17 was responsible for increased Th1 cell-mediated pathology (25). In humans, a negative association with parasite-induced IL-17 production by PBMCs from patients with cutaneous leishmaniasis and muco-cutaneous leishmaniasis infected with L. braziliensis has been reported (26,27).…”
mentioning
confidence: 99%